Elgar companion to regulating AI and big data in emergent economies - Findlay, Mark editor; Ong, Li Mi editor; Zhang, Wenxi, (Cheltenham,UK Northampton : Edward Elgar Publishing, 2023)
"Committed to highlighting the regulatory needs and priorities of emerging economies in the context of AI and big data, this expertly crafted Companion explores the nature and role of regulation in the Global South from a techo-dependent societal perspective. It not only amplifies the unspoken and underrepresented voices in AI and data regulation scholarly discourse, but also provides a novel approach to otherwise recipient economies in an age of digital transformation. Covering central themes such as regulatory flows, self-regulation and AI ethics, contextual regulation, and regulatory devices, the Companion brings together an array of eminent academics from across the globe. Chapters critically reflect on the nature and role of regulation, charting the tapestry of regulatory influence and capacity, values, and relationships of dependence and vulnerability attendant on advancing AI and mass data sharing. The regulatory challenges facing emerging economies and post-colonial societies are examined, and contributors engage new frames of thinking and solutions from perspectives beyond the interests of techno-colonialism. International and interdisciplinary in scope, this Companion will be an interesting read for academics and students in development studies, law and development, innovation and technology studies, and regulation and governance"-- "Committed to highlighting the regulatory needs and priorities of emerging economies in the context of AI and big data, this expertly crafted Companion explores the nature and role of regulation in the Global South from a techo-dependent societal perspective. It not only amplifies the unspoken and underrepresented voices in AI and data regulation scholarly discourse, but also provides a novel approach to otherwise recipient economies in an age of digital transformation. Covering central themes such as regulatory flows, self-regulation and AI ethics, contextual regulation, and regulatory devices, the Companion brings together an array of eminent academics from across the globe. Chapters critically reflect on the nature and role of regulation, charting the tapestry of regulatory influence and capacity, values, and relationships of dependence and vulnerability attendant on advancing AI and mass data sharing. The regulatory challenges facing emerging economies and post-colonial societies are examined, and contributors engage new frames of thinking and solutions from perspectives beyond the interests of techno-colonialism. International and interdisciplinary in scope, this Companion will be an interesting read for academics and students in development studies, law and development, innovation and technology studies, and regulation and governance"--